Recruitment of East Himalayan Oak (Quercus serrata) in Western Himalaya - Bahl, R. K.; Pandey, R. K. (Indian Forester, 1989)
North-east Himalayan Oak, Quercus serrata Thunb. was introduced in Western Himalayas at different locations in Himachal Praiesh. At 4 years of age, average shoot heigbt was observed to be between 151-279 cm with 10-21 cm diameter. Considerable variation in growth rate was evident between different locations, which was due to differences in altitude. Low altitude areas (790-1140 m ASL) were found to be more suitable for the recruitment of Q. serrata in Himachal Pradesh.